Investigating derivative usage decisions of Brazilian companies - Golhiardi, Marcelo (2021)
The purpose of this dissertation is twofold: first, to identify what are the main reasons that lead companies to use derivatives, and second, to understand whether the use of derivatives by Brazilian companies increases the value of the company. We find evidence that firms that use financial derivative instruments, in particular for financial speculation, present a higher market value than firms that do not use them. Regarding the motivations for hedging, the size of the companies, the distribution of dividends to its shareholders, the share of revenues from abroad, capital expenditures on growth opportunities, and capital expenditures on branding and reputation increase the probability of companies engaging in hedging activities. Regarding the motivations for speculating, capital expenditures on growth opportunities, higher profitability, and more financial leverage reduce the probability that the firm engages in speculating activities with derivatives. This study contributes to complement previous studies carried out in Brazil, published by Rossi (2008) and Serafini and Sheng (2011), by focusing on the different purposes for derivative usage, as well as on analyzing the drivers for these different types of usage of derivatives. Our findings can help investors better assess companies within their portfolios to improve their returns by selecting firms that better manage their derivative usage. Also, it provides a framework that helps investors identify the drivers that lead companies to engage in derivative usage.